PENGARUH FILSAFAT YUNANI PADA PERKEMBANGAN TEOLOGI ISLAM ABAD PERTENGAHAN - Muhammad Zaki (Yayasan An-Nur Meunara Baro, 2025)
This article explores the significant influence of Greek philosophy on the development of Islamic theology during the medieval period. This interaction began in the Abbasid era through large-scale translation movements at Bayt al-Hikmah, which enabled the works of Plato, Aristotle, and Plotinus to enter the Islamic intellectual tradition. Muslim philosophers such as al-Kindi, al-Farabi, Ibn Sina, and Ibn Rushd not only adopted but also transformed key concepts of Greek philosophy such as the prime mover, emanation theory, and Aristotelian logic within the framework of Islamic metaphysics and theology. On the other hand, the integration of these ideas provoked critical responses from theological scholars, particularly from the Ashʿarite school and traditionalist circles, who rejected some metaphysical aspects of Greek philosophy deemed incompatible with Islamic revelation. This study employs a historical-philosophical approach and textual analysis of primary sources from both Greek philosophy and classical Islamic theology. The findings reveal that despite tensions between rationalism and scriptural authority, a constructive synthesis occurred, enriching theological argumentation. Aristotelian logic became a crucial methodological tool in the rational development of kalam within the Ashʿarite and Maturidite traditions. Moreover, the intellectual legacy of this synthesis contributed not only to the systematization of Islamic theology but also played a vital role in the transmission of knowledge to the West during the European Renaissance. This article affirms that Greek philosophy served as a dialectical partner in the construction of a dynamic Islamic intellectual tradition.